A Survey – Wearable Antenna Techniques and its Applications - Vinothkanna, R. (Recent Research Reviews Journal, 2022)
Smart Antenna is an array of antennas which uses the smart signal processing algorithms to track and locate the client device using the direction of arrival of a signal. Smart Wearable Antennas are designed to function while being worn. Wearable antennas are used within the context of Wireless Body Area Networks. The wearable antenna is high in efficiency, miniature in size, and simple in structure, and is implemented with electrical performance and polarization effects, which helps in healthcare, medical and military applications, smart glasses, sensor devices in sports, etc. This research study reviews different wearable antenna technologies such as wearable textile antenna, microstrip antenna and wearable antenna array. Furthermore, the integrated different next generation antennas are also discussed.
Keywords: Wireless Body Area Networks; Wearable Antennas; Smart Antenna; Microstrip Antenna